Musculoskeletal Infections In Pediatric Patients at Saiful Anwar General Hospital: Observation for 5 Years - Satria Prabawa Perkasa Suhaedy; Felix Cendikiawan; Muhammad Abduh; Alva Pribadi; Panji Sananta (Jurnal Berkala Kesehatan, 2021)
Musculoskeletal infection in pediatrics is a disorder that can cause significant disability. Follow-up evaluation is mandatory to ensure good long-term results. However, there is no data regarding this in Indonesia. The purpose of this study was to describe the epidemiology of musculoskeletal infections in pediatrics in Indonesia. This study is an observational epidemiological study of all pediatric musculoskeletal infection patients at Saiful Anwar Hospital Malang, Indonesia. All data were obtained from the database of the Department of Orthopedics and Traumatology of Saiful Anwar Hospital for the 2016-2020 period. A total of 71 patients were included in this study. The data collected were age, gender, diagnosis, anatomic location, treatment, and outcome. There were 48 (67.60%) male and 23 (32.39%) female patients in our study. The most frequent site of infection was the lower extremities (57.75%), followed by the spine (35.21%). In this study, the highest incidence occurred in children (6-12 years) followed by adolescents (12-18 years). This study also showed similar findings to other studies for the site of infection where the most common infection involved the lower extremities. Multidisciplinary treatment must be undertaken to reach an accurate diagnosis, determine the need for surgery, and monitor response to treatment.